Pengembangan Metode Penstrukturan Masalah Berbasis Cognitive Map dan Strategic Choice Approach dan Penerapannya pada Masalah Manajemen Rantai Pasokan - Iwan Mumin Basarah; Sani Susanto (Jurnal Teknik Industri, 2016)
The problem structuring methods used to deal with complex  and ill-structured problems. One of the method of structuring ill-structured  problem is the Strategic Choice Approach (SCA), while one of the problems of complex and ill-structuredproblems  is a supply chain management problems. This research proposes the use of a cognitive map as a base application of SCA on the problems of supply chain management at PT X, a leading manufacturing company in Indonesia. Three main results of this study are structuring problems, choosing of the top priority problems, and choosing of troubleshooting options among other identified options.